Freedomland : Co-op City and the story of New York - Sammartino, Annemarie (Three Hills, an imprint of Cornell University Press, 2022)
"Tells the story of the 35 towers and 236 townhouses of Co-op City in the Bronx from the perspective of the men and women who dreamed it and built it, and of the ordinary people who lived there"--